background image

From this, as easy to show,

h

v

f

and

h

v A 

FCD

B

. If

g

v

f

^

g

v A 

FCD

B

for a

g

2

FCD

(

A

;

B

)

then dom

g

v A

, im

g

v B

,

h

g

iX

=

B u h

g

i

(

A u X

)

v B u h

f

i

(

A u X

) =

D

id

B

FCD

(

B

)

E

h

f

i

D

id

A

FCD

(

A

)

E

X

=

h

h

iX

;

and similarly

h

g

¡

1

iX v h

h

¡

1

iX

.

g

v

h

. So

h

=

f

u

(

FCD

B

)

.

Corollary 15.68.

Let

A

,

B

be sets of lters over boolean lattices. For every

f

2

FCD

(

A

;

B

)

and

A 2

A

we have

f

j

A

=

f

u

(

FCD

1

B

)

.

Proof.

f

u

(

FCD

1

B

) =

id

1

B

FCD

(

B

)

f

id

A

FCD

(

A

)

=

f

id

A

FCD

(

A

)

=

f

j

A

.

Corollary 15.69.

Let

A

,

B

be sets of lters over boolean lattices. For every

f

2

FCD

(

A

;

B

)

and

A 2

A

,

B 2

B

we have

f

/

FCD

B , A

[

f

]

B

:

Proof.

f

/

FCD

B ,

f

u

(

FCD

B

) =

/ 0

FCD

(

A

;

B

)

,

f

u

(

FCD

(

A

;

B

)

B

)

1

A

=

/ 0

B

,

D

id

B

FCD

(

B

)

f

id

A

FCD

(

A

)

E

1

A

=

/ 0

B

,

D

id

B

FCD

(

B

)

E

h

f

i

D

id

A

FCD

(

A

)

E

1

A

=

/ 0

B

, B u h

f

i

(

A u

1

A

) =

/ 0

B

,

B u h

f

iA

=

/ 0

B

, A

[

f

]

B

.

Theorem 15.70.

Let

A

,

B

be sets of lters over boolean lattices. Then the poset

FCD

(

A

;

B

)

is

separable.

Proof.

Let

f ; g

2

FCD

(

A

;

B

)

and

f

=

/

g

. By the theorem

15.12

[

f

]=

/ [

g

]

. That is there exist

x; y

2

A

such that

x

[

f

]

y

<

x

[

g

]

y

that is

f

u

(

x

FCD

y

) =

/ 0

FCD

(

A

;

B

)

<

g

u

(

x

FCD

y

) =

/ 0

FCD

(

A

;

B

)

. Thus

FCD

(

A

;

B

)

is separable.

Theorem 15.71.

Let

A

and

B

be posets of lters over boolean lattices. If

S

2

P

(

A

B

)

then

l

fA 

FCD

B j

(

A

;

B

)

2

S

g

=

l

dom

S

FCD

l

im

S:

Proof.

If

x

2

atoms

A

then by the theorem

15.59

l

fA 

FCD

B j

(

A

;

B

)

2

S

g

x

=

l

fhA 

FCD

Bi

x

j

(

A

;

B

)

2

S

g

:

If

x

u

d

dom

S

=

/ 0

A

then

8

(

A

;

B

)

2

S

: (

x

u A

=

/ 0

A

^ hA 

FCD

Bi

x

=

B

);

fhA 

FCD

Bi

x

j

(

A

;

B

)

2

S

g

=

im

S

;

if

x

u

d

dom

S

= 0

A

then

9

(

A

;

B

)

2

S

: (

x

u A

= 0

A

^ hA 

FCD

Bi

x

= 0

B

);

fhA 

FCD

Bi

x

j

(

A

;

B

)

2

S

g 3

0

B

:

So

l

fA 

FCD

B j

(

A

;

B

)

2

S

g

x

=

(

d

im

S

if

x

u

d

dom

S

=

/ 0

A

;

0

B

if

x

u

d

dom

S

= 0

A

:

From this by theorem

15.58

the statement of our theorem follows.

Corollary 15.72.

Let

A

and

B

be posets of lters over boolean lattices.

For every

A

0

;

A

1

2

A

and

B

0

;

B

1

2

B

(

A

0

FCD

B

0

)

u

(

A

1

FCD

B

1

) = (

A

0

u A

1

)

FCD

(

B

0

u B

1

)

:

Proof.

(

A

0

FCD

B

0

)

u

(

A

1

FCD

B

1

) =

d

fA

0

FCD

B

0

;

A

1

FCD

B

1

g

what is by the last theorem

equal to

(

A

0

u A

1

)

FCD

(

B

0

u B

1

)

.

15.9 Direct product of elements

189